1999
DOI: 10.1211/0022357991777010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aldo-keto Reductases by Phenobarbital Alters Metabolism, Pharmacokinetics and Toxicity of Doxorubicin in Rats

Abstract: Doxorubicin is an effective anticancer agent that is limited by numerous adverse effects, cardiotoxicity causing the most concern. Its alcohol metabolite, doxorubicinol, and free radicals have been implicated in the aetiology of this toxicity. This study was based on the premise that inhibition of aldo-keto reductases would improve the efficacy of doxorubicin by reducing its toxic metabolites and modifying its pharmacokinetics. We assessed the effect of in-vitro inhibition of aldo-keto reductases on the metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…We showed that both paclitaxel and docetaxel stimulated an NADPH-dependent reduction of doxorubicin to doxorubicinol in isolated human cardiac cytosol (Minotti et al, 2001b), a translational model that obviated potential pitfalls caused by the different enzymology of anthracycline secondary alcohol metabolite formation in laboratory animals versus humans (Maessen et al, 1987;Behnia and Boroujerdi, 1999;Minotti et al, 2004;Salvatorelli et al, 2006). The effect of paclitaxel or docetaxel did not require Cremophor EL or polysorbate 80, nor was it observed on replacing the taxanes with the structurally unrelated tubulin-active Vinca alkaloid vinorelbine; this showed that stimulation of doxorubicinol formation was inherently related to the taxoid backbone of paclitaxel or docetaxel (Minotti et al, 2001b).…”
mentioning
confidence: 99%
“…We showed that both paclitaxel and docetaxel stimulated an NADPH-dependent reduction of doxorubicin to doxorubicinol in isolated human cardiac cytosol (Minotti et al, 2001b), a translational model that obviated potential pitfalls caused by the different enzymology of anthracycline secondary alcohol metabolite formation in laboratory animals versus humans (Maessen et al, 1987;Behnia and Boroujerdi, 1999;Minotti et al, 2004;Salvatorelli et al, 2006). The effect of paclitaxel or docetaxel did not require Cremophor EL or polysorbate 80, nor was it observed on replacing the taxanes with the structurally unrelated tubulin-active Vinca alkaloid vinorelbine; this showed that stimulation of doxorubicinol formation was inherently related to the taxoid backbone of paclitaxel or docetaxel (Minotti et al, 2001b).…”
mentioning
confidence: 99%
“…Furthermore, increases in aldose reductase protein have also been observed in carcinoma cells 14,15 . Importantly, it has been suggested that increased aldose reductase expression and intracellular sorbitol accumulation may be partly responsible for reduced efficacy of chemotherapeutic drugs used to treat breast cancer 6 . In such cases, aldose reductase activity appears to influence cell growth and the response of tumor cells to anti-cancer drugs.…”
Section: Appendicesmentioning
confidence: 99%
“…Although the mechanism by which this side effect develops is not yet identified, evidence implicates metabolism as an important factor (Olson and Mushlin, 1990). Following DOX or DAUN administration, the C-13 alcohol metabolites, DOXol and DAUNol, are the major identified metabolites (Takanashi and Bachur, 1976), and these metabolites are speculated to be responsible for causing cardiac tissue damage (Del Tacca et al, 1985;Boucek et al, 1987;Cusack et al, 1993;Behnia and Boroujerdi, 1999;Olson et al, 2003;Sacco et al, 2003).…”
mentioning
confidence: 99%
“…Inhibition of the anthracycline-metabolizing enzymes is suggested as a strategy for avoiding treatment-related cardiotoxicity (Behnia and Boroujerdi, 1999), and chemical inhibitors for reductases and anthracycline derivatives that are metabolically less labile have been explored for their potential roles as safer alternatives to the currently used anthracycline drug treatments. In part, the success of these strategies relies on accurately identifying the enzymes responsible for anthracycline metabolism.…”
mentioning
confidence: 99%